Poetry as a spiritual exercise - Lopes, Marcos (2014)
The poetry is knowledge and radical encounter with the sensible world. The relentless bond among the sensible and the intelligible corresponds to a spiritual exercise, which is not synonymous with religious belief, but the fundamental requirement for the apprehension of the meaning of human life. This article aims to establish a dialogue among three Portuguese poets (Ruy Belo, José Tolentino Mendonça and Daniel Faria) who made their poetry an authentic spiritual exercise.